Phytochemical screening of Alstonia venenata leaf and bark extracts and their antimicrobial activities - Bagheri, Gholamreza; Ayatollahi, Seyed Abdulmajid; Ramírez-Alarcón, Karina; Salehi, Bahare; Mohammadi, Rojan; Rahmani, Afrooz; Martorell, Miquel; Sharifi-Rad, Javad; Sheibani, Mohammad; Amarowicz, Ryszard (Cellular and Molecular Biology, 2020)
Alstonia venenata is a plant commonly found in South India and used in traditional medicine. The aim of this study was to characterize the phytochemicals present in A. venenata leaf and bark extracts and study their antimicrobial activities. Solvent extractions with Soxhlet apparatus of leaves and bark were obtained using hexane, benzene, isopropanol, methanol, and water. The crude extracts were concentrated and screened for qualitative phytochemical content and analyzed by thin layer chromatography. The antibacterial, antifungal and antiviral activities of crude extracts were measured by in vitro methods. Alkaloids, carbohydrates, tannins, phenolic compounds, terpenoids, cardiac glycosides and amino acids were found in the different crude extracts analyzed. Isopropanol extracts showed antifungal activity and it was more pronounced in the bark extract than the leaf extract. Moreover, the isopropanol extract exhibited antibacterial and antiviral activity. In conclusion, the leaves and bark of A. venenata have antimicrobial components which are more present in the isopropanol fraction.